Differences in Body Composition of Children 12-15 Years Living at Highland and Lowland in Kulonprogo Yogyakarta - Janatin Hastuti, Alwahyulhaq Jati Sasmito, Ari Kurniawat (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Body composition changes during growth. From age of 12 to 15 years one of the important growth periods occurs indicated by adolescent growth spurt in the circum pubertal age. Measuring body composition of children necessary, since the different components of body composition vary with age, sex, and maturity status. Many studies showed that high altitude affects morphological and physiological characters of children which are reflected in a different growth pattern.Objective: The aim of this research was to investigate the differences of body composition of children at age of 12-15 years in Samigaluh highland and Galur lowland in Kulonprogo Regency Yogyakarta Province.Methods: The research was done on 502 children of 12-15 years old, boys and girls, consisted of 232 children living in Samigaluh highland and 270 children living in Galur lowland. The children were healthy and did not have physical and mental disorder. Some measurements were taken on the children, included weight, and stature, skin fold thickness of triceps, infrascapula, suprailiaca, abdominal, thigh, and calf. The components of body composition were then estimated from those measurements, i.e. Body Mass Index, lean body weight, total fat, and percentage of body fat. Statistical analysis by t-test and Pearson correlation were used in this research.Results: Body mass index, total fat and percentage of body fat of girls in highland and lowland populations were greater than the boys, but they were smaller on lean body mass. Girls of lowland population were greater on total fat, but they were slight smaller on body mass index except at age of 12 years. Lean body weight and percentage of body fat in girls of both populations were not different except at age of 12 years. Boys living in highland were smaller than their peers in lowland on most of body composition components except total fat.Conclusions: Estimated body composition of children of highland and lowland in Kulonprogo were different between boys and girls. In comparison to the girls, boys showed greater difference in body composition. However, by the increase of age, growth patterns of body composition components on both populations were similar, except total fat of highland boys.Keywords: body composition, children, highland, lowland